Candida Auris: An Updated Review for Nursing Interventions and Management Protocols - Otayn , AMNAH Ali; Alnasser , Hanem Adel Abdullah; ALZAHRANI, ADNAN MUSA; Alharbi, Noha Muaybid; Aseri, Amnah Ahmad; Mahzari, Ibrahim Mohammed; Alosaimi , Mubarak Juhayyim Mohammed; ALOTAIBI, IBRAHIM AYIDH; AL-Hareegi , Gosnh Saad; Alabyad, Jehan Abdullah Mohammad; Almohammady , Ghadeer Mohammad Eid; ALAZMI, DHAIFALLAH MUBARAK EID; et al. (Journal of Ecohumanism, 2024)
Background: Candida auris (C. auris) is an emerging multidrug-resistant fungal pathogen that poses a significant global health threat, particularly in healthcare settings. First identified in 2009, C. auris has rapidly spread to over 35 countries, causing invasive infections with high mortality rates, especially among immunocompromised patients. Its resistance to multiple antifungal classes, misidentification by standard diagnostic methods, and ability to persist on surfaces complicate its management and control. Aim: This review aims to provide an updated overview of C. auris, focusing on its epidemiology, pathophysiology, resistance mechanisms, and clinical management. It also highlights the critical role of nursing interventions and infection control protocols in preventing and managing C. auris outbreaks. Methods: The review synthesizes current literature on C. auris, including its etiology, transmission patterns, virulence factors, and antifungal resistance mechanisms. It also examines diagnostic challenges, treatment strategies, and nursing management protocols. Emphasis is placed on infection control measures, such as hand hygiene, environmental disinfection, and patient isolation, to mitigate the spread of C. auris in healthcare settings. Results: C. auris is highly transmissible in nosocomial environments, with resistance to azoles, echinocandins, and polyenes complicating treatment. Early diagnosis using advanced molecular methods, such as MALDI-TOF MS and DNA sequencing, is crucial for effective management. Nursing interventions, including strict adherence to infection control protocols, patient monitoring, and education, are essential to prevent transmission and improve patient outcomes. Conclusion: C. auris represents a formidable challenge due to its multidrug resistance and ability to spread rapidly in healthcare settings. A multidisciplinary approach, including early diagnosis, targeted antifungal therapy, and robust infection control measures, is critical for managing C. auris infections. Nurses play a pivotal role in implementing these strategies to reduce transmission and improve patient care